Low-Dose Ibutilide Combined with Catheter Ablation of Persistent Atrial Fibrillation: Procedural Impact and Clinical Outcome - Xue-Rong Sun; Ying Tian; Ashok Shah; Xian-Dong Yin; Liang Shi; Yan-Jiang Wang; Xiao-Qing Liu; Meleze Hocini; Michel Haissaguerre; Xin-Chun Yang; Xing-Peng Liu (Cardiology Research and Practice)
Background. In patients with persistent atrial fibrillation (AF), the procedural and clinical outcomes of ablation combined with infusion of antiarrhythmic drug are unknown. Objectives. To determine the impact of low-dose ibutilide after circumferential pulmonary vein isolation (CPVI) and/or left atrial (LA) substrate modification on acute procedural and clinical outcome of persistent AF. Methods. In a prospective cohort of 135 consecutive patients with persistent AF, intravenous 0.25 mg ibutilide was administered 3 days before the procedure and intraprocedurally, if required, after CPVI and/or additional LA substrate modification of sites with continuous, rapid or fractionated, and low-voltage (0.05–0.3 mv) atrial activity. Results. Persistent AF was terminated by CPVI alone (n=15) or CPVI + ibutilide (n=32) in 47 (34.8%) patients (CPVI responders). Additional LA substrate modification without (n=33) or with subsequent administration of 0.25 mg ibutilide (n=19) terminated AF in another 52 (38.5%) patients (substrate modification responders). Sinus rhythm was restored by electrical cardioversion in the remaining 36 (26.7%) patients (nonresponders). The mean LA substrate ablation time was 14 ± 6 minutes. At follow-up of 24 ± 10 months, the rates of freedom from atrial tachyarrhythmias among the responders in CPVI and substrate modification groups were mutually comparable (66.0% and 69.2%) and higher than among the nonresponders (36.1%; P<0.01). Among the responders, there was no difference in clinical outcome between patients whose persistent AF was terminated without or with low-dose ibutilide. Conclusion. Administration of low-dose ibutilide during ablation of persistent AF may allow select patients wherein substrate ablation is not or minimally required to optimize procedural and clinical outcomes.